PENGARUH KUALITAS LAYANAN DAN KEPUASAN PADA KEGIATAN EVENT OLAHRAGA PERUSAHAAN REPETITIF TERHADAP KEBAHAGIAAN KARYAWAN PT PERTAMINA (PERSERO) REFINERY UNIT III - Daniswara Krisna Prabatha (President University, 2020)
This research aims to determine the effect of event’s service quality and event’s satisfaction of company sport repetitive event on employee happiness at PT. Pertamina (Persero) Refinery Unit III Plaju. The population in this study is all employees of PT. Pertamina (Persero) Refinery Unit III Plaju as many as 1024 employees. The samples used in the study were as many as 156 employees as respondents obtained by probability sampling with proportional random sampling method. Data collection methods use questionnaires and data processing techniques used through multiple linear regression analysis. Results of multiple linear regression analysis showed that event’s service quality has a positive and significant effect on the employee’s happiness at PT Pertamina (Persero) Refinery Unit III as well as the event’s satisfaction is positive and significant to the employee’s happiness at PT Pertamina (Persero) Refinery Unit III. From those variables, the most dominant variable affecting employee happiness in this study was the service quality. It is recommended to PT Pertamina (Persero) Refinery Unit III to enhance service quality aspects at the future company sport repetitive events, including interaction quality, physical environment quality and outcome quality. For further researchers, it is advisable to add other variables including performance, work environment, compensation and achievements.